Figure 1 from: Norarfan AF, Azreena Mokti SS, Taha H, Amin M, Ali M, Arai T (2021) DNA barcoding of a tropical anguillid eel, Anguilla bicolor (Actinopterygii: Anguilliformes), in Indo-Pacific region and notes on its population structure. Zoologia 38: 1-7. https://doi.org/10.3897/zoologia.38.e59332 - Norarfan, Ahmad Fathi; Azreena Mokti, Siti Shazwani; Taha, Hussein; Amin, Muhamad; Ali, Muhamad; Arai, Takaomi (Zenodo, 2021)
Figure 1 Map of sampling locations of Anguilla bicolor bicolor from Indonesia and Malaysia and A. bicolor pacifica from the Philippines. Sampling locations are shown in red. Locations of Banda Aceh in northern Sumatra of Indonesia, Sukabumi in western Java of Indonesia, Andhra Pradesh in southeast India, Langkawi and Penang islands of northwest Peninsular Malaysia, Cebu in the Philippines, and Yangon of Myanmar, which were used in molecular phylogenetic and haplotype network analyses, are shown in blue. Base map is downloaded from http://viewer.nationalmap.gov/viewer (USGS 2020).